Revolutionizing Hydrocarbon Education: How Concept Maps Improve Chemistry Outcomes - Erni Batu Bara; Majid Shabani Mahalli (Journal of Chemical Learning Innovation, 2024)
Purpose of the study: Purpose of the study This is For know There is whether or not improvement results Study students in class chemistry especially on the subject discussion hydrocarbon with use map draft . Methodology: Subject in study This is students of X Asy-Syafiiyah Air Tiris Islamic High School with amount student as many as 22 people. While object study This is improvement results Study chemistry in the main discussion Hydrocarbons . Subjects studied​ is lesson chemistry in the main discussion Hydrocarbons . Types of data obtained in study This that is types of qualitative data and quantitative data , which consist of from the result data learning and data on teacher and student activities . Data collection techniques in research This use documentation , observation , and interviews . Main Findings: Based on results research , use map draft For increase results Study students on the subject discussion hydrocarbons in class X MA Asy-Syafiiyah Watertiris Kampar District , Kampar Regency makes student more active and improving performance students . Data collection with using post test , repeat daily each cycle and documentation . Author give number For every cycle , namely before action 59.00%, Cycle I 67.50%, Cycle II 81.50%. Novelty/Originality of this study:Concept map-based learning methods revolutionize the way chemistry is taught, making hydrocarbon material easier to understand and apply.